Complexation of 26-Mer Amylose with Egg Yolk Lipids with Different Numbers of Tails Using a Molecular Dynamics Simulation - Shangyuan Sang; Xueming Xu; Xiao Zhu; Ganesan Narsimhan (Foods, 2021)
A molecular dynamics simulation of mixtures of 26-mer amylose with three different egg yolk lipids, namely, cholesterol, triglyceride and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC), demonstrated the formation of a stable complex. The 26-mer amylose fluctuated between a coiled and an extended helical conformation. The complex was a V-type amylose complex, with the hydrophobic tail of the lipids being inside the hydrophobic helical cavity of the amylose. The number of glucose units per turn was six for the two helical regions of the amylose-POPC complex and the palmitoyl tail region of the amylose-triglyceride complex. This value was eight for the cholesterol and the two-tail helical region in the amylose-triglyceride complex. Two tails of the POPC were in two different hydrophobic helical regions of the 26-mer amylose, whereas the palmitoyl tail of the triglyceride lay in one hydrophobic helical region and the linoleoyl and oleoyl tails both lay in another helical region, and the cross-sectional area of the latter was larger than the former to accommodate the two tails. The radii of the gyration of the complex were lower for all three cases compared to that of one single amylose. In addition, the stability of the complexes was ranked in the following order: POPC < cholesterol < triglyceride, with their average binding energy being −97.83, −134.09, and −198.35 kJ/mol, respectively.